Distribution of bacterial keratitis and emerging resistance to antibiotics in China from 2001 to 2004 - Chen Zhang (Dove Medical Press, 2008)
Chen Zhang, Yanchuang Liang, Shijing Deng, Zhiqun Wang, Ran Li, Xuguang SunDepartment of Ocular Microbiology, Beijing Institute of Ophthalmology, Beijing Tongren hospital, Capital University of Medical Science, BeijingObjective: To study on the distribution of bacterial keratitis isolates and the resistance to antibiotics in China from 2001 to 2004.Methods: 1985 specimens from the bacterial keratitis at the Beijing Tong Ren Eye Center were cultured and identified. In vitro susceptibility testing of positive isolates to antibiotics was determined by the Kirby-Bauer disk diffusion method and interpreted according to Clinical and Laboratory Standards Institute.Results: Out of 1985 specimens, 279 were culture positive. The percentage of positive culture was 14.06%. Gram-positive cocci and gram-negative bacilli represented 42.65% (119/270) and 35.13% (98/279) respectively. Pseudomonas sp. was the most common organism (20.07%), followed by Corynebacterium sp. (16.85%) and Staphylococcus epidermidis (13.98%). Resistance to ofloxacin, ciprofloxacin, levofloxacin, and tobramycin was 20.2%, 35.9%, 15.5%, and 29.4% respectively. Gram-negative bacilli showed higher resistance to ciprofloxacin. Staphycoccus sp. revealed significant resistance to ciprofloxacin. Streptococcus sp. showed high resistance to tobramycin. The resistance of isolates from older patients (≥60Y) to ciproloxacin, levofloxacin, and tobramycin was higher than that from adult patients (>14 to 59Y).Conclusion: Staphylococcus sp., Pseudomonas sp., and Corynebacterium sp. were the most common bacterial keratitis isolates in China. Attentions should be paid to the increase of the resistance to levofloxacin.Keywords: bacteria keratitis resistance